1974
DOI: 10.1111/j.1365-2125.1974.tb00216.x
|View full text |Cite
|
Sign up to set email alerts
|

The ASSESSMENT OF Β‐ADRENOCEPTOR BLOCKING DRUGS IN HYPERTHYROIDISM

Abstract: Intravenous propranolol and practolol both reduced resting supine heart rate in patients with hyperthyroidism. Propranolol produced a significantly greater reduction than practolol, which did not have a dose-dependent effect. 2 The effect of these drugs on resting heart rate was much less than their effect on the tachycardias produced both by severe exercise and by standing upright in hyperthyroid patients. Propranolol again produced a significantly greater reduction than practolol in each situation, but pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1975
1975
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Though suppression of the tachycardia associated with severe exercise (where there is little or no vagal influence) is the ideal way of assessing betablockade, some investigators have found that standing produces an assessment of beta-blockade not dissimilar from that obtained by more elaborate methods, i.e. severe exercise (Carruthers et al, 1974;Kofi Ekue et al, 1974). Moreover, such a simple method is easy to use in outpatient clinics-as in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Though suppression of the tachycardia associated with severe exercise (where there is little or no vagal influence) is the ideal way of assessing betablockade, some investigators have found that standing produces an assessment of beta-blockade not dissimilar from that obtained by more elaborate methods, i.e. severe exercise (Carruthers et al, 1974;Kofi Ekue et al, 1974). Moreover, such a simple method is easy to use in outpatient clinics-as in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, however, Carruthers, Ghosal, McDevitt, Nelson & Shanks (1974) demonstrated that practolol did have a dose-dependent effect in hyperthyroid patients on the tachycardia induced by severe excercise, an accepted method for demonstrating the effectiveness of,-adrenoceptor blocking drugs (Brick, Hutchison, McDevitt, Roddie & Shanks, 1968;Coltart & Shand, 1970 Three preferences were thus determinedpatient's subjective preference, observer's objective preference without heart rate and observer's preference including heart rate -for each comparison (propranolol and placebo, practolol and placebo, and propranolol and practolol) and these were submitted to sequential analysis using the method described by Armitage (1960).…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of propranolol on resting heart rate has been used in a number of studies (3,10,13), this does not give a reliable index of the drug's effect in hyperthyroidism (13).…”
Section: Discussionmentioning
confidence: 99%
“…Some thyrotoxic patients, however, have heart rates at this level before therapy; thus, the use of absolute resting heart rate (3,10) gives no indication of patient drug compliance, and in other patients with severe thyrotoxicosis it may not be possible to reduce the pulse rate to this level, as the intrinsic heart rate (after pharmacological denervation) is increased in thyrotoxic patients (21). In addition, resting heart rates do not give a reliable index of /?-adrenergic blockade in thyrotoxic patients (13), and thyroid storm has been described (11,12) in patients with resting pulse rates of less than 90 beats/min.…”
Section: H O^ ^* ^J ^J ^^ ^^ Co Co O L *™H ^* ^H ^H ^* P H R"h ^Hmentioning
confidence: 94%
See 1 more Smart Citation